The influence of Islamic philosophy on European thought in the Middle Ages - Hussam Ahmed Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Islamic philosophy is considered one of the most important philosophies that influenced human thought during the Middle Ages. Islamic philosophy has always been an important bridge for the transmission and development of human knowledge, effectively contributing to the formation of Western thought during the Middle Ages and beyond. This research aims to shed light on the pivotal role Islamic philosophy played in shaping and building European thought during the Middle Ages. To achieve the research objective, the analytical approach was employed to identify the influence of Islamic philosophy on European thought in the Middle Ages. The study concluded that translation played a significant role in transmitting Islamic philosophy to Europe during the Middle Ages. Muslim scholars translated Greek, Roman, Persian, and Indian philosophical works into Arabic. Europeans benefited from Arab philosophers and their divisions of the sciences, and subsequently reconsidered their divisions. It is also evident that Muslim philosophers established an original approach to the study of Islamic philosophy, which was effectively reflected in European thought.DOI: https://doi.org/10.54633/2333-024-057-012